2021
DOI: 10.1088/1755-1315/709/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Milk Production, Consumption and Digestibility of Ration Based on The Palm Kernel Cake, Tithonia (Tithonia Diversifolia) and Corn Waste on Etawa Crossbreed Dairy Goat

Abstract: This study aims to evaluate milk production, consumption and digestibility of rations in Etawa Crossbreed Dairy Goats (ECDG) fed with concentrate of palm kernel cake (CPKC), tithonia (Tithonia diversifolia) and corn waste. The design used was a completely randomized design with 4 treatment rations and 5 replications. Treatment A = 7.5 kg titonia + 4 kg tofu waste, B = 7.5 kg tithonia + 2 kg tofu waste + 1.2 kg CPKC, C = 2 kg corn waste + 5.5 kg tithonia + 2 kg tofu waste + 1.2 kg of CPKC, D = 4 kg of corn wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…This observation finds support in the research of Pazla et al (2018b), who argued that nutrient intake is contingent on both the dry matter quantity in the consumed feed and the nutritional composition of the provided feed. The study also uncovered that livestock could consume significant quantities of feed, which is influenced by their individual requirements, in accordance with the findings of Arief et al (2021aArief et al ( , 2021b. Arief et al (2018a) reported that the number of feeds needed by livestock, particularly goats, is influenced by their feeding capacity and total body weight.…”
Section: Treatment Of Feed Intake In Etawa Crossbreed Dairy Goatssupporting
confidence: 83%
“…This observation finds support in the research of Pazla et al (2018b), who argued that nutrient intake is contingent on both the dry matter quantity in the consumed feed and the nutritional composition of the provided feed. The study also uncovered that livestock could consume significant quantities of feed, which is influenced by their individual requirements, in accordance with the findings of Arief et al (2021aArief et al ( , 2021b. Arief et al (2018a) reported that the number of feeds needed by livestock, particularly goats, is influenced by their feeding capacity and total body weight.…”
Section: Treatment Of Feed Intake In Etawa Crossbreed Dairy Goatssupporting
confidence: 83%
“…Feed consumption will increase if the forage provided contains several plant variations. Arief et al (2021) reported an increase in goat consumption by giving two types of forage compared to one type of forage alone. Goats quite like fermented tithonia because it smells good.…”
Section: Methodsmentioning
confidence: 99%
“…The terms related to probiotics are synbiotic, kefir, prebiotic, milk yield, lactic acid bacteria (lab), ration, milk quality, dadiah, fermentation, and lactobacillus plantarum, which indicates that research on microbial contaminants in milk is one of the most widely carried out is the probiotic object which has a product distribution with research themes ranging as mentioned above. Synbiotic is a combination of prebiotics and probiotics which is believed to have a synergistic effect by inhibiting the growth of pathogenic bacteria and increasing the growth of beneficial organisms [15]. Milk yield is information used to measure the productivity of a farm [16].…”
Section: Network Visualization Revmentioning
confidence: 99%